Generation of circular dichroism from superposed porphyrin films. Issue 5 (23rd February 2021) - Takechi, Hideaki; Watarai, Hitoshi
Abstract: Circular dichroism (CD) was observed from the superposed porphyrin deposited glass plates, which were prepared by the vapor deposition of achiral porphyrin molecules and oriented to one direction by rubbing parallel to the surface of plate. The CD spectra depended on the twisted angle between the plates and the number of plates superposed. The observed CD spectra agreed with the simulated ones by the Mueller matrices superposition calculation using the observed linear dichroism spectra and linear birefringence spectra of each plate. Abstract :